Selective Sensing of Ammonium Ion Over Other Biologically Important Ammonia Derivatives by a Coumarin‐Based ϵ‐Amino Ester. Issue 2 (9th January 2018) - Pramanik, Apurba; Abbasi, Mazharul; Maji, Krishnendu; Nandi, Sujay Kumar; Datta, Rupak; Haldar, Debasish
Abstract: Ammonium ions are a waste product of the amino acidsmetabolism  of animals and finally converted to urea in liver. Specific sensing of ammonium ion may helpful for diagnosis of liver malfunction. An efficient coumarin‐based ϵ‐amino ester has been synthesized and the specific sensing of ammonium ion has been investigated. From single crystal X‐ray diffraction analysis, the amide group is out of the plane of the central aromatic core of the compound but the ester group is co‐planar and the compound self‐assembled to form supramolecular duplex‐like structure. The coumarin‐based ϵ‐amino ester successfully discriminates ammonium ion over other biologically important ammonia derivative such as D‐ glucosamine, ATP, glycine, L‐glutamic acid, L‐aspertic acid and urea. The coumarin‐based ϵ‐amino ester shows excellent selectivity as turn‐off optical sensor for ammonium ion. Further the biocompatibility of the coumarin‐based ϵ‐amino ester was studied by DNA binding assay and cellular uptake by mouse macrophage cell line RAW264.7. Abstract : Coumarin‐based ϵ‐amino ester has been developed and the specific sensing of ammonium ion over other biologically important ammonia derivative such as D‐ glucosamine, ATP, glycine, L‐glutamic acid, L‐aspertic acid and urea has been investigated. In solid state, the compound formed hydrogen bonded parallel sheet which further assemble to form supramolecular duplex‐like structure through π‐π stacking. The biocompatibility of the compound was studied by DNA binding assay and cellular uptake by mouse macrophage cell line RAW264.7